2013
DOI: 10.1111/mec.12404
|View full text |Cite
|
Sign up to set email alerts
|

Genetic drift outweighs natural selection at toll‐like receptor (TLR) immunity loci in a re‐introduced population of a threatened species

Abstract: During population establishment, genetic drift can be the key driver of changes in genetic diversity, particularly while the population is small. However, natural selection can also play a role in shaping diversity at functionally important loci. We used a well-studied, re-introduced population of the threatened Stewart Island robin (N = 722 pedigreed individuals) to determine whether selection shaped genetic diversity at innate immunity toll-like receptor (TLR) genes, over a 9-year period of population growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 68 publications
5
94
1
Order By: Relevance
“…Across birds, extensive evidence for episodic positive selection on TLR-4 leucine-rich repeat regions has been observed (Grueber et al, 2014). On a scale more comparable to our study, a genetic bottleneck at the time of introduction influenced variation in the TLR-4 exon sequence in a passerine introduced to New Zealand (Grueber et al, 2013). The only study so far to consider selection on drivers of gene expression in wild animals involved the mannan-binding lectin promoter in roe deer (Capreolus capreolus) (Quéméré et al, 2015).…”
Section: The Role Of Tlr-4 Expression In Kenya House Sparrow Expansionmentioning
confidence: 56%
“…Across birds, extensive evidence for episodic positive selection on TLR-4 leucine-rich repeat regions has been observed (Grueber et al, 2014). On a scale more comparable to our study, a genetic bottleneck at the time of introduction influenced variation in the TLR-4 exon sequence in a passerine introduced to New Zealand (Grueber et al, 2013). The only study so far to consider selection on drivers of gene expression in wild animals involved the mannan-binding lectin promoter in roe deer (Capreolus capreolus) (Quéméré et al, 2015).…”
Section: The Role Of Tlr-4 Expression In Kenya House Sparrow Expansionmentioning
confidence: 56%
“…Drift is the predominant evolutionary force shaping genetic variation in small populations Miller and Lambert 2004;Jensen et al 2013), and its effects on genetic variation often outweigh the influence of selection (Miller and Lambert 2004;Alcaide 2010;Grueber et al 2013). Nevertheless, various studies have shown that within small natural populations, variation at specific key loci can be elevated above that of the genome-wide average, and be maintained across bottleneck events as a result of balancing selection (Aguilar et al 2004;Tompkins 2007;van Oosterhout et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may have potential consequences for survival, fitness, fecundity and reproductive success of water voles and consequently population viability and persistence. As such, it is an ecologically meaningful locus and understanding its dynamics in populations is useful in a conservation context (Hedrick 2001;Seddon 2010;Thomas 2011;Oliver and Piertney 2012;Grueber et al 2013). This reinforces the point made by Acevedo-Whitehouse and Cunningham (2006) that the MHC is not the only region of the immunogenome that is important and should be characterised in an ecological context.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are an essential family of type 1 transmembrane glycoproteins that act as pattern recognition receptors (PRRs) and play an important role in the innate immune response (Akira et al 2001;Brownlie and Allan 2011;Grueber et al 2013;Fornusková et al 2013). They are involved in the initial recognition of invading infectious agents (Tschirren et al 2013) and act as a host's front-line defence against a wide range of pathogens (Uematsu and Akira 2008;Iwasaki and Medzhitov 2010;Alcaide and Edwards 2011).…”
Section: Introductionmentioning
confidence: 99%